A neuronal DNA damage response is detected at the earliest stages of Alzheimer's neuropathology and correlates with cognitive impairment in the Medical Research Council's Cognitive Function and Ageing Study ageing brain cohort. (23rd April 2015) - Simpson, Julie E.; Ince, Paul G.; Matthews, Fiona E.; Shaw, Pamela J.; Heath, Paul R.; Brayne, Carol; Garwood, Claire; Higginbottom, Adrian; Wharton, Stephen B.; MRC Cognitive Function and Ageing Neuropathology Study Group
<x xml:space="preserve">Abstract</x> Aims Population‐based studies have shown that approximately 20% of the ageing population (aged 65 years and over) with dementia have little or no classical Alzheimer‐type neuropathology. Cumulative DNA damage and a reduced capacity of DNA repair may result in neuronal dysfunction and contribute to cognitive impairment independent of Alzheimer‐type pathology in the ageing brain. Methods We investigated expression of the DNA damage response (DDR)‐associated molecules γH2AX and DNA‐PKcs using immunohistochemistry and western blotting, and senescence‐associated β‐galactosidase in the frontal association neocortex of cases with low levels of Alzheimer‐type pathology (Braak & Braak stage 0–II), and explored their relationship to cognitive impairment in a population‐representative sample from the Medical Research Council's Cognitive Function and Ageing Study cohort. Results Increases in both γH2AX+ (rs = −0.36, P = 0.025) and DNA‐PKcs+ (rs = −0.39, P = 0.01) neuronal counts were associated with a lower Mini‐Mental State Examination score. Increasing levels of senescence associated‐β‐gal+ pyramidal neurones were weakly associated with the total number of DNA‐PKcs+ neurones (P = 0.08), but not with traditional senescence‐associated signalling molecules, including p53 and p16. Conclusion The association between the neuronal DDR and cognitive impairment, independent of AD pathology in the ageing brain, may be suggestive of a causal link via neuronal dysfunction.